تسريع مهارة الكلام للأطفال عبر استراتيجيات التعلم الممتع في مؤسسة "أبيا" التعليمية غير الرسمية بسورابايا - Roby Nurwanda; Angger Bimantara (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study addresses the systemic barriers in early childhood Arabic education, particularly low speaking skills (maharah kalam) driven by rote-learning and speaking anxiety, by exploring the joyful learning strategies implemented at the "ABIA" non-formal institution in Surabaya. Employing a qualitative approach with an exploratory case study design, data were collected through participant observation, documentation, and semi-structured interviews with one teacher and nine purposively selected primary students, analyzed using an interactive model. The findings reveal that the institution successfully eliminated language anxiety by constructing a supportive linguistic ecosystem. Programmatically, the teacher integrated four pivotal strategies: the Direct Method using visual aids to bypass mental translation, the Dialogue Method utilizing short functional texts, Drilling for rapid response, and Language Games/Role-Play for spontaneous speech. This study concludes that incorporating communicative approaches into flexible, active, and playful activities successfully transitions children from passive receivers to confident, independent language producers. Theoretically and practically, these results provide a practical pedagogical blueprint for curriculum developers to redesign early Arabic instructions from monotonous memorization to communicative, joyful learning ecosystems.